Digital Payment, E-Commerce, and Social Media Effects on Halal Culinary Purchase Decisions: Evidence from Yogyakarta, Indonesia - Ifa Azzahra Farhatannisa; Miftahus Surur (Islamiconomic : Jurnal Ekonomi Islam, 2025)
The development of science and technology in the food sector enables food or beverage production to be carried out quickly and efficiently. One aspect that has received attention is the need for halal food or drinks. The concept of "halal" in Islam refers to anything that is permissible under Islamic law. This study aims to analyze the influence of e-payment, e-commerce, and social media on halal culinary purchase decisions in Yogyakarta (Case Study of Dimsum Narawi Consumers). The method used in this study is quantitative, with data collected as primary data. The population in this study consists of visitors who have purchased Dimsum Narawi in Yogyakarta. The sampling technique used is purposive sampling, with a sample of 100 respondents, and Levene's test is used. Primary data were collected through a questionnaire using Google Forms. The data analysis technique uses SmartPLS version 3.0. The results showed that the e-payment variable (X1) and social media (X3) affected purchase decisions, whereas the e-commerce variable (X2) did not.